Accounting in Its Age of Stagnation. - Winjum, James (The Accounting Review, 1970)
The article determines the functioning of double-entry bookkeeping during the Age of Stagnation of accounting. Most studies in accounting history have focused on tracing the evolution of accounting techniques and methodology; little effort has been devoted to a consideration of what accounting's role in the historical process has been. The early double entry authors enumerated the advantages of double entry, presenting a series of benefits to be derived from its use ranging from peace of mind and freedom from illness to the profitable employment of assets. One aspect of capital is its balancing function in the initial inventory or ending balance sheet; the role it plays in expressing, in one compact figure, the investment of the owner. This lack of interest in periodic calculations of total profits was mitigated by the practice of venture accounting. The treatises and account books of this period reveal an emphasis on individual activities, whether temporary partnerships, factorage activities, trade in specific commodities or to specific ports, or investments in lands, ships, or securities. Accounting